Caracterização do gene vasa em Rhamdia quelen para aplicações biotecnológicas - Ricci, Juliana Morena Bonita [UNESP] (2015)
The vasa gene encodes a protein that belongs to protein family called DEAD (Asp-Glu-Ala-Asp) Box, which is constituted of ATP-dependent RNA helicases. This protein is extremely conserved among the organisms, and its role is associated with RNA metabolism. In the majority of the investigated species, vasa expression is restricted to the germline cells. Different methods (such as knockdown, knockout and mutation) to address vasa's role have demonstrated that vasa is crucial for germ cell development. In this study, we have characterized the full cDNA of vasa from a native species, R. quelen (Heptapteridae Siluriformes). Comparative analysis using the protein sequence has demonstrated that Vasa is highly conserved along the evolution. Moreover, we have evaluated through RT-PCR and qRT-PCR Rqvasa expression in different tissues, showing that vasa transcripts are exclusively expressed in the R. quelen gonads, specifically in the germinal cells RT-PCR and qRT-PCR analysis during embryonic and larval development have shown that Rqvasa is maternally inherited and its expression decreased during development. in situ hybridization techniques performed in whole embryos and larvae allowed to study the primordial germ cells (PGCs) migratory process towards the gonadal ridge. This work has characterized for the first time the full length cDNA of vasa, describing its expression patterns during R. quelen embryonic development as well as the PGCs migratory process in this species. Our results will contribute for the basic reproductive biology of this native species, and will support studies using vasa in different biotechnological studies, such as sterility, transgenesis (vasa